2020
DOI: 10.1177/1756284820931739
|View full text |Cite
|
Sign up to set email alerts
|

Review of the epidemiology and burden of ulcerative colitis in Latin America

Abstract: The incidence and prevalence of ulcerative colitis (UC) has been reported to be rising in newly industrialised regions, such as Latin America. Here, we review data from published studies reporting demographics and clinical aspects of UC in Latin America to further understand epidemiology and disease burden. The incidence and prevalence of UC in Latin America varied between regions and studies, ranging between 0.04 to 8.00/100,000 and 0.23 to 76.1/100,000, respectively, and generally increased over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 44 publications
3
17
0
Order By: Relevance
“…In terms of the sex distribution of IBD, we found a higher prevalence among females compared to that among male, which is in line with the results of several previous studies, such as the one carried out by Souza in 2002 (7,10,(23)(24)(25) . However, across all the individual years observed during the study period (2010-2019), we found similar incidence rates for IBD between male and female patients.…”
Section: Discussionsupporting
confidence: 92%
“…In terms of the sex distribution of IBD, we found a higher prevalence among females compared to that among male, which is in line with the results of several previous studies, such as the one carried out by Souza in 2002 (7,10,(23)(24)(25) . However, across all the individual years observed during the study period (2010-2019), we found similar incidence rates for IBD between male and female patients.…”
Section: Discussionsupporting
confidence: 92%
“…UC is an intractable, cancer-prone, refractory gastrointestinal disease, since Stephen et al first described the pathology of diseases such as colitis or idiopathic colitis [ 1 ]. In recent years, the incidence of the disease has been increasing, and it has been classified as one of the intractable diseases by the World Health Organization (WHO) [ 2 ]. Currently, there is no effective treatment for UC, and the current main treatment is also based on controlling the inflammatory response of the intestine and controlling complications.…”
Section: Introductionmentioning
confidence: 99%
“…Ulcerative colitis (UC), a kind of chronic nonspecific inflammatory bowel disease, mainly involves intestinal inflammation and epithelial injury, including the rectum, colonic mucosa, and submucosa, accompanied by some common colitis symptoms, i.e., rectal bleeding, diarrhea, abdominal pain, weight loss, and even increased colorectal cancer risk . Currently, the rise of global industrialization and the change in East–West dietary habits have been paralleled by a dramatic increase in the incidence of UC worldwide, resulting in a substantial burden on public healthcare .…”
Section: Introductionmentioning
confidence: 99%